Designing Tactile Vocabularies for Human-Computer Interaction - Oliveira, Victor; Maciel, Anderson (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2015)
This paper summarizes our study of tactile languages in humancomputer interaction. We intended to analyze how the choices made during the design process of tactile vocabularies would affect the user performance on an interactive task. Therefore, we have developed and tested different sets of tactile signals for aid navigation in virtual environments. It leaded us to fashion a novel approach for vibrotactile prefixation. Through this experimental-driven study, we attempted to effects of multisensory stimulation, perception, learning and interpretation of tactile sequences, and masking caused by multiple vibrations in a same locus. The presented results should be useful for other designers to produce usable and expressive tactile interfaces.